Temporal and concentration effects of isoflurane anaesthesia on intestinal tissue oxygenation and perfusion in horses. Issue 1 (July 2015) - Hopster, K.; Hopster-Iversen, C.; Geburek, F.; Rohn, K.; Kästner, S.B.R.
Highlights: Depth but no duration of isoflurane anaesthesia influences global and gastrointestinal perfusion and oxygenation. There is linear correlation between isoflurane concentration and central perfusion. There is non-linear correlation between isoflurane concentration and gastrointestinal perfusion. Gastrointestinal perfusion seems to be preserved until MAP threshold of about 60 mmHg or CI of 50 mL/kg/min. Abstract: The aim of this study was to assess the effect of duration of anaesthesia and concentration of isoflurane on global perfusion as well as intestinal microperfusion and oxygenation. Nine Warmblood horses were premedicated with xylazine; anaesthesia was induced with midazolam and ketamine, and maintained with isoflurane. Horses were ventilated to normocapnia. During 7 h of anaesthesia, mean arterial blood pressures (MAP), heart rate, central venous pressure, pulmonary artery pressure, expiratory isoflurane concentration (ET Iso) and cardiac output using lithium dilution were measured; cardiac index (CI) was calculated. Intestinal microperfusion and oxygenation were measured using laser Doppler flowmetry and white-light spectrophotometry. Surface probes were placed via median laparotomy on the serosal and mucosal site of the jejunum and the pelvic flexion of the colon. After 3 h of constant ET Iso (1.4%), ET Iso was increased in 0.2% increments up to 2.4%, followed by a decrease to 1.2% and an increase to 1.4%. The CI and MAP decreased continuously with increasing ET Iso to 40 ± 5 mL/kg/min and 52 ± 8 mmHg, respectively. Microperfusion and oxygenation remained unchanged until an ET Iso of 2.0% resulted in CI and MAP of 48 ± 5 mL/kg/min and 62 ± 6 mmHg, respectively, and then decreased rapidly. When ET Iso decreased back to baseline, CI, MAP, microperfusion and oxygenation recovered to baseline. Isoflurane concentration but not duration of isoflurane anaesthesia influenced central and intestinal oxygenation and perfusion in healthy horses. Under isoflurane, intestinal perfusion appeared to be preserved until a threshold MAP or blood flow was reached.